Ответ:
Объяснение:
........
[tex] \frac{4}{7} ×( \frac{1}{2} x− \frac{2}{3} )=2x−4 \frac{1}{3} \\ \frac{4}{14} x - \frac{8}{21} = 2x - \frac{13}{3} \\ \frac{4}{14}x - 2x = - \frac{13}{3} + \frac{8}{21} \\ x( \frac{4}{14} - \frac{2}{1} ) = - \frac{13 \times 7}{21} + \frac{8}{21} \\ x( \frac{4 - 24}{14} ) = \frac{ - 91 + 8}{21} \\ - \frac{20}{14} x = - \frac{83}{21} \\ x = \frac{83}{21} \div \frac{20}{14} \\ x = \frac{83}{21} \times \frac{14}{20} \\ x = \frac{83}{3} \times \frac{1}{10} \\ x = \frac{83}{30} = 2 \frac{23}{30} [/tex]
[tex]x = 2 \frac{23}{30} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
........
[tex] \frac{4}{7} ×( \frac{1}{2} x− \frac{2}{3} )=2x−4 \frac{1}{3} \\ \frac{4}{14} x - \frac{8}{21} = 2x - \frac{13}{3} \\ \frac{4}{14}x - 2x = - \frac{13}{3} + \frac{8}{21} \\ x( \frac{4}{14} - \frac{2}{1} ) = - \frac{13 \times 7}{21} + \frac{8}{21} \\ x( \frac{4 - 24}{14} ) = \frac{ - 91 + 8}{21} \\ - \frac{20}{14} x = - \frac{83}{21} \\ x = \frac{83}{21} \div \frac{20}{14} \\ x = \frac{83}{21} \times \frac{14}{20} \\ x = \frac{83}{3} \times \frac{1}{10} \\ x = \frac{83}{30} = 2 \frac{23}{30} [/tex]
[tex]x = 2 \frac{23}{30} [/tex]